Room Temperature NO2-Sensing Properties of N-Doped ZnO Nanoparticles Activated by UV-Vis Light - Angelo Ferlazzo; Giovanni Neri; Andrea Donato; Giovanni Gugliandolo; Mariangela Latino (Sensors)
Zinc oxide nanoparticles (ZnO NPs) with varying levels of nitrogen (N) doping were synthesized using a straightforward sol–gel approach. The morphology and microstructure of the N-doped ZnO NPs were examined through techniques such as SEM, XRD, photoluminescence, and Raman spectroscopy. The characterization revealed visible changes in the morphology and microstructure resulting from the incorporation of nitrogen into the ZnO lattice. These N-doped ZnO NPs were used in the fabrication of conductometric gas sensors designed to operate at room temperature (RT) for detecting low concentrations of NO2 in the air, under LED UV-Vis irradiation (λ = 400 nm). The influence of nitrogen doping on sensor performance was systematically studied. The findings indicate that N-doping effectively enhances ZnO-based sensors’ ability to detect NO2 at RT, achieving a notable response (S = R/R0) of approximately 18 when exposed to 5 ppm of NO2. These improvements in gas-sensing capabilities are attributed to the reduction in particle size and the narrowing of the optical band gap.